The genetic and pharmacogenomic landscape of snoRNAs in human cancer - Yaoming Liu; Hang Ruan; Shengli Li; Youqiong Ye; Wei Hong; Jing Gong; Zhao Zhang; Ying Jing; Xiulan Zhang; Lixia Diao; Leng Han (Molecular Cancer, 2020)
Abstract Emerging evidence has revealed significant roles for small nucleolar RNAs (snoRNAs) in tumorigenesis. However, the genetic and pharmacogenomic landscape of snoRNAs has not been characterized. Using the genotype and snoRNA expression data from The Cancer Genome Atlas, we characterized the effects of genetic variants on snoRNAs across 29 cancer types and further linked related alleles with patient survival as well as genome-wide association study risk loci. Furthermore, we characterized the impact of snoRNA expression on drug response in patients to facilitate the clinical utility of snoRNAs in cancer. We also developed a user-friendly data resource, GPSno ( http://hanlab.uth.edu/GPSno ), with multiple modules for researchers to visualize, browse, and download multi-dimensional data. Our study provides a comprehensive genetic and pharmacogenomic landscape of snoRNAs, which will shed light on future clinical considerations for the development of snoRNA-based targeted therapies.